Oral Health Care Provision System and Dental Education in Georgia (2014-2017) - Gigineishvili, Elene; Margvelashvili-Malament, Mariam (Caucasus Journal of Health Sciences and Public Health, 2019)
This article presents an overview of oral health-care delivery in Georgia since 2014.Paper describes the dental education sources, shows the statistics of licensed dentists and number of dentists of seven sub-specialties registered in Georgia. National statistics office of Georgia (Geostat), Ministry of Labor Health and Social Affairs and National Centre for disease Control (NCDC), Georgian legislation Matsne were used as the information source.